The bond that burns - Boleyn, Briar (Boleyn, Briar. Bloodwing Academy, 2025)
At Bloodwing Academy, blood is currency, but a dragon's legacy is priceless--and as dangerous as fire.I thought surviving my first year in Bloodwing's deadly halls would be enough. I was wrong. I accidentally woke a dragon--a creature of myth, of death, of fire. Now every highblood house wants control over me and the dragon's legacy I carry. But here's the truth: I have no control. I'm bluffing my way through every encounter, trying to keep everyone from realizing that I'm not the one pulling the dragon's strings.And then there's Blake Drakharrow. I thought he was on my side, that I might even be able to trust him. But he betrayed me. Now I'm his only blood source. How messed up is that? In a place like Bloodwing, where power and survival are everything, this bond may well be the death of us both. Unless I can find a way to end it.In this world of vampires, dragons, and lies, there are no happy endings. Just legends--and the darkness it takes to make them.